The Decline of Tramp Shipping - Gregg, E. S. (Quarterly Journal of Economics, 1926)
Journal Article The Decline of Tramp Shipping Get access E. S. Gregg E. S. Gregg Department of Commerce, Washington Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 40, Issue 2, February 1926, Pages 338–346, https://doi.org/10.2307/1884623 Published: 01 February 1926